Modelling of Parameters of Building Earthing Devices - Bagdanavičius, N.; Eidukas, D.; Drabatiukas, A.; Kilius, Š (Elektronika ir Elektrotechnika, 2009)
When researching the process of the lightning current propagation through the elements of the earthing device imitational and computational modeling methods are used. The computer program was created for the investigation of the dependences of the earthing resistances and pulse coefficient on the specific soil resistance, length of the earthing device and lightning current magnitude. Using this program earthing resistance investigations were accomplished for various soil types and electrodes of different dimensions. Determined parameters are suitable for the design and calculations of the earthing devices. Ill. 9, bibl. 11 (in English; summaries in English, Russian and Lithuanian).